Autocognición sobre civismo y ciudadanía, de estudiantes de pedagogía en Historia, Geografía y Educación Cívica en una universidad chilena - Sáez Geoffroy, Andrés; Parra-Díaz, Joel; Herrera Gómez, Fernando (Universidad de Costa Rica, 2020)
This research arises from the need to know how the teaching staff of Pedagogy in History, Geography and Civic Education of a Chilean university, conceives elements of civics and citizenship. The objective of this article is to identify the relationships between selfcognition on civics and citizenship and the academic performance of teachers in training. The results are analyzed according to the curricular progress of the study subjects, with the purpose of identifying if the curriculum affects the development of these civic competences. The research was carried out in 2018 under a quantitative, cross-sectional approach, with a descriptive and correlational design. The sample was 129 subjects and a stratified probabilistic sampling was used. The scale of the International Study of Civic Education and Citizenship Training of the year 2009. The results show that there is a correlation between the scores in the three categories of the dimension studied and the Accumulative General Average (PGA) of those who participated, not existing at At the same time, differences according to the curricular progress. In this way, a relationship can be established between the development of citizen self-ignition and academic performance, although the curriculum of this career would not favor the development of these competences. Given the particularity of the curriculum of the career studied by those who participated, the results could not be generalized, however this is a study of a subject that is not very much addressed, which allows establishing a base on which other works could be carried out.